RELATIONSHIP OF SEVERAL RISK FACTORS IN PERIODONTITIS: SMOKING, GENDER, AGE AND MICROBIOLOGICAL FINDING - Velitchka Dosseva-Panova; Zdravka Pashova-Tasseva; Antoaneta Mlachkova (Peytchinski Publishing, 2023)
Introduction: Literature data discuss the importance of some risk factors in conjunction with the periodontitis' severity and extent - age, gender, periodontal pathogens, smoking habits, diet, emotional stress, systemic diseases, osteoporosis, medication, and socio-economic status. The role of microorganisms in the initiation and progression of periodontal diseases is well documented at present. The presence of certain bacteria may be related with the elevated risk of periodontitis, as well as with the severity of the destructive process. Aim: Evaluation of the risk factors: smoking, gender and age in relation to the bacterial finding in periodontitis. Material and methods: In this study, 20 subjects with periodontitis were included. Important periodontal parameters were evaluated to confirm the diagnosis. Subgingival plaque samples were taken from periodontal sites with probing depth ≥6mm. The presence of periodontal pathogens was assessed according to gender, age and smoking. Results: In the current study, significant differences were found between the microbial parameters and the gender and age of the patients. Two pathogenic bacteria - Treponema denticola and Prevotella intermedia, showed significantly higher levels in the male gender - p=0.05 and p=0.07, respectively. Periodontal pathogens Tannerellaforsythiaand Peptostreptococcusmicros were found in elevated levels in individuals older than 47 years. Conclusion: No significant differences were found in the bacterial presence between smokers and non-smokers. Only Treponemadenticola was found in elevated levels in smokers (p=0.9). The male gender may be associated with representatives of periodontal microbiota.